KARAKTERISTIK DAN KERAGAMAN MORFOLOGIS BEBERAPA AKSESI PADI SAWAH LOKAL DATARAN TINGGI KABUPATEN MAMASA DAN POTENSI PENGEMBANGANNYA - Marthen P Sirappa; Religius Heryanto; Nurdiah Husnah (Jurnal Ilmiah Maju, 2019)
Rice is a major component in the national food security system. Indonesia is one of the sources of rice diversity, where the Center for Rice Research has about 17,000 germplasm accessions. This diverse germplasm represents the basic capital for assembly and repair of rice varieties. Activity inventory and characterization of local rice paddy Mamasa done in 2014 and 2015 with survey method. The inventory and characterization data were tabulated and then analyzed descriptively. The result of inventory and characterization shows that in Batupapan and Siwi village, Nosu sub-district, Mamasa district was found 9 types of accession of local highland rice. Of the nine accessions of local rices, pare Tongoran is a type of rice belonging to Indica and eight other species (Pare Kamandang, Kuse, Riri, Lotting, Sassan, Bae' Putih, Bae' Merah/Ba'da and Bittoen) including Javanica. Three accessions that have many chicks, namely pare Kamandang (15-22 tillers/clumps), pare Tongaran (20-22 tillers/clumps), and pare Bittoen (18-19 tillers/clumps). The number of grains per grain ranged from 100-237 grains, panicle length of 24 -33 cm, and weight of 1000 seeds 25 - 31.6 g. Based on the color of rice, the accession is classified as rice of red rice (Pare Kuse, Bae' Merah / Ba'da, Tongoran and Kamandang) and one accession belonging to black rice (pare Lotting), four other accessions belonging to white rice (Bittoen, Bae' Putih, Sassan and Riri). One accession belongs to aromatic rice (pare Sassan). Accession of upland rice which has potential to be developed as a source of germplasm such as pare Lotting (black rice, health rice, and many used for social events), pare Tongoran and Kamandang (red rice, many tillers, health rice, number of grain/panicle are many; pare Sassan (aromatics, weight of 1000 grain seeds is high). Keywords: characteristic, morphological diversity, potency, local rice, highland.